Ground motion simulations in Quito (Ecuador) due to major earthquakes from the subduction zone. Issue 3 (4th February 2022) - Courboulex, Francoise; Castro-Cruz, David Alejandro; Laurendeau, Aurore; Bonilla, Luis Fabian; Alvarado, Alexandra; Bertrand, Etienne
SUMMARY: In 1906, an earthquake with a magnitude estimated between M w 8.4 and 8.8 occurred in the subduction zone along the coast of Ecuador and Colombia. This earthquake caused extensive damage on the coast but had a rather small impact on the capital city of Quito, situated 180 km away. At that time, the city of Quito extended over a small area with a few thousand inhabitants, while today it stretches over 40 km and has a population of over 3 million, with most of the city built without paraseismic regulations. The aim of this study is to obtain new insights on the impact that large earthquakes from the subduction zone would have on the city today. This question is crucial since we know that the city of Quito is prone to site effects and that the southern part of the city amplifies seismic waves at low frequencies, around 0.3–0.4 Hz. In April 2016, an M w 7.8 earthquake occurred on the subduction interface in the Pedernales area. This event was the first large earthquake in the city of Quito to be well recorded by 13 stations of the permanent accelerometric network (RENAC). In this study, we take advantage of this data set (main shock and large aftershock recordings) to (1) test an empirical Green's function blind simulation approach where the input stress drop is taken from a global catalogue of source time functions, (2) compare the synthetic accelerograms and ground motion values we obtain for an M w 7.8 earthquake with the actual recordings of the Pedernales earthquake and then (3) simulate larger earthquakes of M w 8.2 and 8.5 from the subduction zone. For M w 7.8 simulations, our approach allows a good reproduction of the ground motions in the whole frequency bands and properly takes into account site effects. For M w 8.2 and 8.5 simulations, we obtain for the stations in the southern part of the basin, larger values at low frequencies than the predicted motion given by ground motion models. These values, although high, should be supported by new or recent buildings if they are constructed respecting the building code that applies in Quito. Therefore, for this type of strong but distant earthquake, the seismic standards appear to be well suited and it is imperative to ensure that they are well considered in the design of the new buildings to be constructed, especially in the southern part of the expanding city.